Enhancing the Quality of Reporting in Corporate Social Responsibility Guidance Documents: The Roles of ISO 26000, Global Reporting Initiative and CSR‐Sustainability Monitor1. (June 2017) - Sethi, S. Prakash; Rovenpor, Janet L.; Demir, Mert
Abstract: The intent of this article is to review the phenomenal growth of Corporate Social Responsibility reports published by large corporations around the world. The reports provide companies with an opportunity to inform large segments of society about the impacts of their business operations on the environmental, socio‐political, and governmental (regulatory) aspects of a society. The mostly voluntary nature of these reports, however, places the burden on the corporations creating them to (a) provide an adequate amount of information, (b) cover all the major issues that are relevant to the company and industry, and (c) provide measures of assurance as to the accuracy of information. In this article, we compare and examine three institutional approaches that have played an important role toward improving the quality and consistency of these reports. The institutions involved are ISO 26000, Global Reporting Initiative (GRI), and Corporate Social Responsibility (CSR)‐Sustainability Monitor. We intend to show their different approaches to guiding CSR reporting, and assess their relative strengths and limitations.